Notes on Philosophy of Logic - de Oliveira, Gilson Maicá (2019)
In this paper we discuss some aspects of logic in present days. The primary proposal is to show the evolution of this discipline.  We begin with a brief introduction where we sketch what we mean by the term “logic”. In the next section we explore and discuss what we consider some of the key research areas of current logic. Finally, we conclude with some observations about non-classical logics and its impacts on philosophy. For a detail research about logic and others aspects related to it, see the references at the end of the paper.